2020
DOI: 10.36709/jipfi.v5i1.10482
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar Fisika Materi Usaha Dan Energi Pada Peserta Didik Kelas X MIA2 SMA Negeri 3 Sampolawa Semester Genap Ta 2018/2019

Abstract: Penelitian ini bertujuan (1)untuk mengetahui peningkatan hasil belajar peserta didik kelas X MIA2 SMA Negeri 3 Sampolawa pada materi usaha dan energi setelah penerapan model pembelajaran discovery learning, (2) Untuk mengetahui ketuntasan hasil belajar peserta didik kelas X MIA2 SMA Negeri 3 Sampolawa pada materi usaha dan energi setelah penerapan model pembelajaran discovery learning. Jenis penelitian ini adalah penelitian tindakan kelas (PTK). Populasi dalam penelitian ini adalah semua peserta didik kelas X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…The results of the study by Jannah et al (2021) also showed that through this discovery learning model, there was a real difference in student learning outcomes seen from the increase in average N-gain. This is also in accordance with research conducted by Dewi et al (2020) said that one of the alternative learning methods that can be applied to improve student learning outcomes is the discovery learning model and the learning method of learners, this is because the discovery learning model encourages learners to develop thinking skills, problem-solving and intellectual skills in real experiences or simulations.…”
Section: Resultssupporting
confidence: 87%
“…The results of the study by Jannah et al (2021) also showed that through this discovery learning model, there was a real difference in student learning outcomes seen from the increase in average N-gain. This is also in accordance with research conducted by Dewi et al (2020) said that one of the alternative learning methods that can be applied to improve student learning outcomes is the discovery learning model and the learning method of learners, this is because the discovery learning model encourages learners to develop thinking skills, problem-solving and intellectual skills in real experiences or simulations.…”
Section: Resultssupporting
confidence: 87%
“…Seorang guru juga harus memiliki keterampilan dan teknik tertentu dalam hal menyampaikan materi yang akan diajarkan agar lebih menarik dan memicu siswa untuk semangat dalam mengikuti pelajaran Fisika. Salah satu keterampilan yang harus dimiliki oleh seorang guru dalam menyampaikan materi adalah dengan menggunakan model dan media pembelajaran yang tepat dan menarik, supaya dapat meningkatkan semangat dan motivasi belajar siswa (Dewi et al, 2021). Salah satu contohnya dengan menerapkan mode learning cycle 7E berbantuan macromedia flash.…”
Section: Pendahuluanunclassified
“…Terakhir fase evaluate dengan bimbingan peneliti, peneliti memberikan kesempatan kepada siswa untuk menyimpulkan secara keseluruhan mengenai materi yang dipelajari (Dewi et al, 2021). Terlihat jelas masing-masing siswa dapat menjawab secara bersama-sama bahkan ada yang menjawab tanpa melihat teks, setelah itu memberikan evaluasi agar lebih memahami konsep dari materi usaha dan energi.…”
Section: Analisis Inferensialunclassified